Influences of simulated gastrointestinal environment on physicochemical properties of gold nanoparticles and their implications on intestinal epithelial permeability. (3rd April 2019) - Jiang, Xiumei; Zhang, Xiaowei; Gray, Patrick; Zheng, Jiwen; Croley, Timothy R.; Fu, Peter P.; Yin, Jun-Jie
Abstract: Gold nanoparticles (Au NPs) hold great promise in food, industrial and biomedical applications due to their unique physicochemical properties. However, influences of the gastrointestinal tract (GIT), a likely route for Au NPs administration, on the physicochemical properties of Au NPs has been rarely evaluated. Here, we investigated the influence of GIT fluids on the physicochemical properties of Au NPs (5, 50, and 100 nm) and their implications on intestinal epithelial permeability in vitro . Au NPs aggregated in fasted gastric fluids and generated hydroxyl radicals in the presence of H2 O2 . Cell studies showed that GIT fluids incubation of Au NPs affected the cellular uptake of Au NPs but did not induce cytotoxicity or disturb the intestinal epithelial permeability.